A decade after the tsunami: preliminary exploration deposit layer of sediment at coast area of Kedah, Malaysia - Siti Habibah Shafiai,; Azuraien Japper @ Jaafar,; Teh, Hee Min; Ahmad Hadi Mohamed Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Study on tsunami deposits is done after a decade of the incident happened at Kedah, Malaysia. This article discusses the characteristics, measurement and thickness of tsunami deposits. It also provides the latest remaining evidences of the tsunami incident including imbrication pattern of cobbles, types of coastal protection and plants at the affected area. Run-up heights and inundation distance were taken into account for field exploration and investigation. This study may provide opportunities to understand how remaining evidences of tsunami could be tracked and recorded.